Online virtual reality system : virtual reality museum / Marlina Meriati @ Munadi - Meriati @ Munadi, Marlina (2004)
The museum website offers online visitors relevant information regarding the museum. Physical visitors can actually see the artifacts. Online visitors can only see the static image of the artifacts in the museum. The museum website also do not offer much choices to the online visitors to communicate with themselves. There are a number of ways online museum can attract more visitors and make the online exploration more interactive and more interesting. This research presents a study of an online virtual reality museum that allows visitors to experience virtual reality on the net, in their web browser. The objectives of the research is to identify the basic characteristics and elements that must exist in the museum website in order for online visitors to communicate, to identify the techniques and elements that must exist in an online virtual reality museum and to develop the prototype of the online virtual reality museum and the prototype of the online interfaces of the museum website. The research will focus on the implementation of virtual reality museum at Muzium Negara Malaysia. The research will also do the modification on the website of Muzium Negara Malaysia. Methodologies implemented in the research are data collections which are comprises of preliminary document collection and survey questionnaires, the analysis of the data and the development of the prototype. The prototype of the discussion board or forum, allows online visitors to not only explore virtual gallery, but also can share their views and communicate with themselves. Then the research has identified techniques and elements that must exist in an online virtual reality museum to develop the prototype of the virtual reality museum. It is clearly that virtual reality has great potential to be used in many applications. As for museum, virtual reality can attract more online visitors to visit the website and to give them more satisfaction and enhance their virtual museum exploration experience. Indirectly it helps to persuade people to learn and educate themselves with our nation's history and heritage. Furthermore it is a great exposure to those who never and want to experience virtual reality technology